GHS-OBAT: Global, open building attribute data reporting age, function, height and compactness at footprint levelEuropean Commission Joint Research Centre Data Catalogue - Pietro Florio; Panagiotis Politis; Katarzyna Krasnodębska; Johannes H. Uhl; Michele Melchiorri; Ana M. Martinez; Georgia Kakoulaki; Martino Pesaresi; Thomas Kemper (Data in Brief)
Detailed geospatial data on building footprints represents a highly valuable source of information, as acknowledged by regulation in Europe. Such datasets are becoming increasingly available in Europe and at global scale, yet they often lack detailed and complete thematic information. Herein, we present the Global Human Settlement – Open Building Attribute Table (GHS-OBAT), a large-scale data integration effort to link thematic attributes to building geometries, namely 2.3 billion openly available building footprints from Overture maps. Specifically, we enrich building footprint geometries with information on the building construction epoch, building height, residential and non-residential building function, and building compactness, from open datasets in the Global Human Settlement Layer data suite. The footprint-level attributes in GHS-OBAT were extracted through vector-raster integration, by applying zonal statistics at the building feature level. The nearly-global coverage of these data adds new dimensions to large-scale building stock analyses, valuable for a wide range of application domains, including disaster risk management, studies of urbanization, energy transition and climate mitigation, affordable housing and renovation, urban design, or real estate.